STUDY LITERATUR: PENGARUH LAMA FERMENTASI TERHADAP KUALITAS RASA DAN TEKSTUR YOGURT - Fany Erlangga Saragih; M. Fazil Mawla Lubis; Putri Rizq Achyari; Yulianti Sinurat; Miftahul Khairani (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This research discusses the effect of fermentation time on the taste and texture quality of yogurt through a literature study approach. Yogurt is a popular fermented milk product because it contains probiotic bacteria, such as Lactobacillus bulgaricus and Streptococcus thermophilus, which can improve digestive health. A fermentation process that utilizes lactic acid bacteria converts lactose into lactic acid, which acts as a natural preservative and determines the taste and texture of yogurt. Fermentation time is a crucial factor that influences the organoleptic and microbiological quality of the product. This research uses data from various scientific journals. The results showed that the duration of fermentation influenced the degree of acidity (pH), viscosity and total lactic acid bacteria in yogurt. Fermentation that is too long can cause a decrease in textural quality due to a decrease in pH approaching the isoelectric point of casein, thereby causing phase separation. This study also found that the concentration of fruit juice in yogurt had a significant effect on the acidity of the product. The conclusion of this study shows that managing the fermentation duration is very important to produce high quality yogurt. It is hoped that this article can be a reference for innovation in making fermented products, as well as a learning resource in biology education.